What the River Said : A Novel - Miller, Sandra Cavallo (Book collections on Project MUSE., 2021)
"In What the River Said: A Novel, the author's final book in her trilogy, is the story of a woman physician at the Grand Canyon Clinic undertaking the challenges of an unusual spate of heart attacks, heavy metal poisoning, and a missing friend, as she and her physician partner temporarily parent a troubled teenager. Their new alliances strengthen as the dark schemes of illicit drug sales become clear"--